Human rights in the market place : the exploitation of rights protection by economic actors - Harding, Christopher, 1951- (Markets and the law., 2008)
The ideology of human rights protection has gained considerable momentum and appears to be an effective lever for bringing about legal change. This book analyzes this strategy in economic and commercial policy and considers the transportation of the 'public law' discourse of basic human rights protection into the 'commercial law' context of economic policy, business activity and corporate behaviour.